1987
DOI: 10.1515/znb-1987-0914
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complexes of Cyclophanes, Part XVI On the Donor Properties of Polynuclear Paracyclophanes and their Sulfur Analogues

Abstract: Visible, 1H NMR and infrared spectra of the charge-transfer (CT) complexes of polynuclear- [2.2]paracyclophanes and their sulfur analogues as electron donors with 2,3-dichloro-5.6-dicyanobenzoquinone (DDQ ), tetracyanoethylene (TCNE) and 9-dicyanom ethylene-2,4,7-trinitrofluorene (DTF) as π-acceptors have been measured. The data indicate an unexpected high basicity of the polynuclear hydrocarbons relative to their sulfur analogues. The types of CT interactions as well as different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The CT interactions between [2 2 ]CPs and TCNQ or TCNE in solution were studied by Mourad et al However, only a limited number of papers on the solid-state structural study of the CT complexes of the cyclophanes have been reported. Trueblood et al reported the crystal structure of the 1:1 complex of [3 2 ](1,4)CP with TCNE .…”
Section: Introductionmentioning
confidence: 99%
“…The CT interactions between [2 2 ]CPs and TCNQ or TCNE in solution were studied by Mourad et al However, only a limited number of papers on the solid-state structural study of the CT complexes of the cyclophanes have been reported. Trueblood et al reported the crystal structure of the 1:1 complex of [3 2 ](1,4)CP with TCNE .…”
Section: Introductionmentioning
confidence: 99%